2016
DOI: 10.3389/fmicb.2016.01996
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of Common Aerobic Anoxygenic Phototrophic Bacteria in a Coastal Aquaculture Area

Abstract: Aerobic anoxygenic phototrophic bacteria (AAnPB) rely on not only heterotrophic but also phototrophic energy gain. AAnPB are known to have high abundance in oligotrophic waters and are the major portion of the bacterial carbon stock in the environment. In a yearlong study in an aquaculture area in the Uwa Sea, Japan, AAnPB, accounted for 4.7 to 24% of the total bacteria by count. Since the cell volume of AAnPB is 2.23 ± 0.674 times larger than the mean for total bacteria, AAnPB biomass is estimated to account … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 30 publications
4
16
0
Order By: Relevance
“…Sato‐Takabe et al. () reported seasonal dynamics of total and AAP bacterial abundances in aquaculture areas similar to the area sampled in the present study and found that higher AAP bacterial abundance tended to coincide with higher water temperature, whereas the abundance of total bacteria was not correlated with water temperature. Generally speaking, temperature is not always a primary factor in determining bacterial growth, but rather some other factors such as salinity, oxygen, organic, and inorganic nutrients can be alternative controlling factors.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Sato‐Takabe et al. () reported seasonal dynamics of total and AAP bacterial abundances in aquaculture areas similar to the area sampled in the present study and found that higher AAP bacterial abundance tended to coincide with higher water temperature, whereas the abundance of total bacteria was not correlated with water temperature. Generally speaking, temperature is not always a primary factor in determining bacterial growth, but rather some other factors such as salinity, oxygen, organic, and inorganic nutrients can be alternative controlling factors.…”
Section: Resultssupporting
confidence: 79%
“…Sato‐Takabe et al. () reported that the DO reaches a saturated level of around 150–200 mmol O 2 per m 3 in summer near aquaculture areas of the Uwa Sea where seawater was collected for the present microcosm and a calculated bacterial respiration rate of 5 mmol O 2 per m 3 /day in coastal mesocosms (Williams, ). This suggests that oxygen available at the start of the experimental period was not depleted and the probability of development of anaerobic anoxygenic species is negligible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The populations of anoxygenic phototrophic bacteria are morphologically and physiologically diverse, indicating an adaptation to the local stratified environments [16]. Indeed, common species of AAP bacteria might be a cosmopolitan species with worldwide distribution that were abundant not only in the oligotrophic open ocean but also in eutrophic aquaculture areas [17]. Some uncertainty remains regarding the the composition of AAP communities from various aquatic habitats.…”
mentioning
confidence: 99%